Morpho-agronomic variability and expression of Sh2 and Bt2 genes in some advanced corn lines under tropical and dryland environment / Fatemeh Abna - Fatemeh , Abna (2018)
Twelve new composite corn lines were characterized and their genotypic and phenotypic variability was studied. Experiments were conducted at two different test locations with tropical and dryland climates (Malaysia and Iran). Initially, all twelve lines were grown for morph-agronomic evaluation in the tropical environment. Ultimately, based on their morphological and physiochemical performance, six outstanding lines were selected for the evaluation of genotypic and phenotypic variability in yield and yield components in the dryland environment. Analysis of variance for all traits except tasseling date showed significant differences among the corn advance lines at the first test location. The highest genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) were observed for yield per plant (30.48%, 38.70%) and ear number per plant (20.01%, 29.35%) respectively. Maximum heritability was obtained for 1000 kernel weight (91.35%), followed by plant height (74.78%) and ear weight (74.31%). Maximum genetic advance was also observed for yield per plant (16116.36), followed by 1000 kernel weight (3342.31) and ear weight (1815.61). At the second test location, the analysis of variance showed significant difference in all traits among the six composite corn lines, except silking date and ear number per plant, which showed no significant difference. The highest GCV and PCV were observed for yield per plant, with 20.56% and 27.89%, respectively. Maximum heritability was obtained for ear length (92.58%), followed by 1000 kernel weight (88.01%) and kernel number per ear (75.27%). Maximum genetic advance was also observed for kernel number per ear (1990.12), followed by yield per plant (491.85) and plant height (344.80). Furthermore, the mean squares from the combined variance analysis of the two test locations showed highly significant variation in genotype, location and interaction between location and genotype for all characteristics studied. Genotypic variation was significant for silking date (MS = 11.89), plant height (MS = 334.69), ear weight (MS = 1654.90), kernel number per ear (MS = 1528.81) and 1000 kernel weight (MS = 2458.67). However, location variation was significant for all characteristics. In fact, both location and genotype interacted significantly with all characteristics except tasseling date and ear length, which showed non-significant variation. In general, based on the DMRT results UM 1 exhibited the highest range of yield and other effective yield components across the two test locations. Furthermore, quantitative real-time PCR was used to measure the RNA transcription levels of various genes including the Sh2 and Bt2 genes and 18s as a housekeeping gene in the leaf and endosperm tissue of six composite corn lines selected at the two test locations. The Sh2 and Bt2 genes presented upregulated expression levels in leaf and endosperm tissue at two different test locations. The correlation coefficient between the expression levels of Sh2 and Bt2 and the morphological traits showed that the expression level of the Bt2 gene in leaf tissue was not significantly associated with any traits, whereas the expression of this gene in endosperm tissue was positively and significantly associated with ear number per plant, ear weight, ear length, kernel number per ear, 1000 kernel weight and yield. Similarly, the expression level of the Sh2 gene in leaf tissue showed no significant correlation with any traits, whereas the expression of this gene in endosperm tissue demonstrated positive and significant association with ear number per plant, ear weight, ear length, 1000 kernel weight and yield.